A systematic literature review on community financing: Avenues for further research - M. Rahmawan Arifin; Bayu Sindhu Raharja; Frank Aligarh; Arif Nugroho (Cogent Business & Management, 2023)
Taking into account the issues on the need for an alternative financing mechanism that can complement and provide solutions to the shortcomings of today's conventional financing mechanisms, this cutting-edge study seeks, through a systematic review analysis, possible avenues for further research on community financing. This review disclosed that previous scholars have failed to address the area of inputs (antecedents). No study was carried out on the processes in the Input-Process-Output/Outcome (IPO) framework. These findings provide ground-breaking information that clarifies the directions of future research. This systematic review employs a combination of a quantitative and qualitative approach to pull together studies on community financing. Involving four stages of data retrieval, article selection, data tabulation, and data analysis by using Publish or Perish (PoP) software. After selecting articles based on the relevance, universality, and quality of the publication, this work employs content analysis to classify articles' topics. This research was restricted to study articles that were indexed by the Scopus and Web of Science (WoS) database that ranged from 2010 to 2021. The result of this research gives an insight to many scholars who want to give more attention to forthcoming research in the field of community financing. Besides, it preserves policymakers as a reference to establish alternative sources of financing by figuring out how community financing works are.
Keywords: 650; Alternative Financing; Financing Strategy; Literature Study; Social Protection; Systematic Literature Review